Integrasi manajemen risiko operasional dan risiko pembiayaan ke dalam kerangka kerja investment risk management (irm) pada perbankan syariah - Marom, Ahmad Aufal (Maliki Interdisciplinary Journal, 2025)
The Islamic banking industry faces significant challenges in managing interconnected operational and financing risks. This article explores the integration of these two risk dimensions within the framework of Investment Risk Management (IRM). Using a qualitative, descriptive library research method, the study finds that integrating operational and financing risk management under IRM enhances efficiency, transparency, and the resilience of Islamic banks amid market uncertainties. Nevertheless, implementation challenges remain, including limited historical data, complex products, and insufficiently trained human resources. To address these, the study recommends developing integrated risk management systems, cross-functional training, and strengthening regulatory and Sharia supervisory roles. This research offers a valuable contribution to formulating effective, Sharia-compliant risk management strategies suited to the evolving financial industry landscape.